1999
DOI: 10.1177/0272431699019002005
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Affection and Helpfulness Toward Parents:

Abstract: This short-term longitudinal investigation examined the 2-year stability of adolescents' prosocial behavior toward mothers and fathers and the predictive role of attachment, conflict, and parental influence in adolescents ' prosocial behavior. At Time 1, adolescents (n = 129) in Grades 6, 8, and 10 and their mothers (n = 126) and fathers (n = 104) completed several questionnaires during two in-home visits. Two years subsequently, families (n = 42) completed the same measures from Time 1. In general, adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 54 publications
4
37
0
3
Order By: Relevance
“…In line with this research, Staub and Sherk (1970) reported more child-reported sharing and helpfulness between friends than nonfriends, and young adolescents claimed that they were more likely to act prosocially toward parents and close friends than toward people in more distant relationships (Bigelow, Tesson, & Lewko, 1992;Eisenberg, 1983). Indeed, a driving impetus in choosing to act prosocially toward a close friend or family member may be an attempt to maintain or improve the relationship (Chapman, Zahn-Waxler, Cooperman, & Iannotti, 1987), which is consistent with a relational approach to prosocial behavior (Eberly & Montemayor, 1999).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…In line with this research, Staub and Sherk (1970) reported more child-reported sharing and helpfulness between friends than nonfriends, and young adolescents claimed that they were more likely to act prosocially toward parents and close friends than toward people in more distant relationships (Bigelow, Tesson, & Lewko, 1992;Eisenberg, 1983). Indeed, a driving impetus in choosing to act prosocially toward a close friend or family member may be an attempt to maintain or improve the relationship (Chapman, Zahn-Waxler, Cooperman, & Iannotti, 1987), which is consistent with a relational approach to prosocial behavior (Eberly & Montemayor, 1999).…”
supporting
confidence: 71%
“…E-mail: laura_walker@byu.edu 1999; Kerr, Beck, Shattuck, Kattar, & Uriburu, 2003;Lindsey, Colwell, Frabutt, Chambers, & MacKinnon-Lewis, 2008). In addition, parents who are involved in their child's activities (particularly prosocial activities) and model helping behavior encourage adolescents to engage in self-motivated prosocial behaviors toward strangers and family (Eberly & Montemayor, 1999;Stukas, Switzer, Dew, Goycoolea, & Simmons, 1999). Research has indicated that parental involvement and connection with the adolescent child work together in promoting moral reasoning and action (Hart, 1988) and has highlighted connection and involvement as key constructs in helpfulness toward parents (Eberly & Montemayor, 1999).…”
Section: Predictors Of Prosocial Behaviormentioning
confidence: 99%
“…Not only will this improve the generalizability of findings, it will also allow the exploration of possible developmental effects when considering the role of parental verbal communication in the development and maintenance of child anxiety. This is important, as there are substantial normative shifts in parent-offspring interactions throughout development, with, for example, increases in the intensity of conflict and decreases in affectionate behaviors as children move into adolescence (Eberly and Montemayor 1999;Laursen et al 1998). Also, when parental behaviors and offspring anxiety disorder status have been compared between children and adolescents, the nature of the association has differed significantly.…”
Section: Representativeness Of Samplesmentioning
confidence: 99%
“…Additionally, another developmental task during this period is to achieve psychological independence from parents, while maintaining connectedness (Allen et al 1994;Grotevant and Cooper 1985). The transformation model suggests that adolescents' affect with their families decreases in early adolescence and then increases in late adolescence (Collins and Laursen 2004;Eberly and Montemayor 1999;Larson et al 1996). Moreover, during adolescence, close friends play important role, and also they begin to surpass parents as adolescents' primary source of social support and contribute in important ways to adolescents' self-concept and well-being (Furman and Buhrmester 1992;La Greca and Harrison 2005).…”
Section: Introductionmentioning
confidence: 99%